Laser induced incandescence soot characterization in farnesane-kerosine wick-fed diffusion flames - Felipe Daniel Tauk Santos (2013)
The entire world is concerned about running out of petroleum in the future, since 90% of all primary energy currently produced is derived from petroleum. Concern also exists about emissions and their impact on the environment, which are a byproduct of the petroleum combustion process. Renewable biofuels are currently seen as good alternatives, which may address both concerns. One of the most promising biofuels, to be used in the world transportation sector on ground and in air, is farnesane (C15H32). Farnesane is a hydrocarbon produced by adding Hydrogen to farnesene, which is extracted from yeast-fermented sugar cane. Among the air pollutants emitted by any combustion process, particulates are most harmful to the environment. Particulates whose size is lower than 100 nm are known as soot. Soot emission also represents a loss of useful energy, negatively affecting the efficiency of any combustion process. This work provides a comparison of the soot emissions of wick-fed diffusion flames from mixtures, in different proportions (0, 5, 10, 20, 50, 75 and 100%), of aviation kerosine (also known as aviation turbine fuel or simply jet fuel) with farnesane, using Laser Induced Incandescence (LII) technique, to evaluate the effects of farnesane in aviation kerosine combustion. Furthermore, a mapping of Polycyclic Aromatic Hydrocarbons (PAH) formation for each blend is provided, since PAH is considered to be the main soot precursor. The results demonstrate that the maximum concentration of soot is located 11 mm above the burner and that the addition of farnesane to kerosine inhibits PAH formation, which causes soot concentration to decrease. Regarding soot particle diameter, they present low axial variation for fuel blends with low quantities of farnesane. Soot particle size decreases at fuel blends with higher proportions of farnesane, and for all fuel blends the smallest soot particle sizes are observed at 11 mm above burner, which is the same height as the highest soot volume fraction.